The incorporation of graphene to enhance mechanical properties of polypropylene self-reinforced polymer composites - Jian Wang; Feiyan Song; Yongzhi Ding; Mingwang Shao (Materials & Design, 2020)
Lightweight, easy recyclability and improved bonding can be achieved by self-reinforced polymer composites (SPC). However, the mechanical properties of SPC are usually limited. This paper describes the incorporation of graphene platelets (GNP) into polypropylene (PP) to produce PP/GNP SPC. PP/GNP fibers were firstly prepared by melt compounding and spinning, and then PP/GNP SPC were produced by film stacking. The thermal, mechanical, and morphological properties of the produced samples were characterized via DSC, WAXD, tensile test, peeling test, optical microscopy, and SEM. The combination of film stacking technology of SPC and nanotechnology of graphene enhanced the mechanical properties significantly. The tensile strength, tensile modulus, and interfacial strength of PP SPC with only 0.062 wt% GNP were increased by 117, 116, and 116%, respectively. The reinforcement is attributed to the high intrinsic mechanical properties of GNP and the self-reinforced mechanism. The spinning promotes the alignment of GNP, and the compaction process induces the in-plane orientation of GNP. In addition, a small number of GNP do not increase the cost significantly.